Alleviation of DSS-induced colitis via Lactobacillus acidophilus treatment in mice. Issue 1 (16th December 2020) - Kim, Woon-Ki; Han, Dae Hee; Jang, You Jin; Park, SungJun; Jang, Sung Jae; Lee, Giljae; Han, Hyuk Seung; Ko, GwangPyo
Abstract : L. acidophilus treatment can modulate immune responses, control the micro-RNA levels and restore the gut microbiota of mice with DSS-induced colitis. Therefore, L. acidophilus treatment could be useful to control inflammatory bowel diseases. Abstract : Gut microbiota play a major role in host physiology and immunity. Inflammatory bowel diseases (IBDs), the important immune-related diseases, can occur through immune system malfunction originating due to dysregulation of the gut microbiota. The aim of this study was to investigate the capabilities and mechanisms of Lactobacillus acidophilus ( L. acidophilus ) KBL402 and KBL409 treatment in the alleviation of colitis using the in vivo dextran sodium sulfate (DSS)-induced colitis mice model. Various colitis symptoms of mice, including disease activity index score [4.55 ± 0.99 ( P < 0.001) and 5.12 ± 0.94 ( P < 0.001), respectively], colon length [6.18 ± 0.43 mm ( P < 0.001) and 6.62 ± 0.47 mm ( P < 0.001), respectively], and colon histological score [(5.33 ± 1.03 ( P < 0.001) and 4.00 ± 0.89 ( P < 0.01), respectively)], were significantly restored with L. acidophilus KBL402 or KBL409 administration (1 × 10 9 colony-forming units) for 8 days. Moreover, inflammatory cytokines, chemokines, and myeloperoxidase were downregulated in mice with L. acidophilus treatment. Upregulation of anti-inflammatory cytokine IL-10 or regulatory T cells were discovered with L. acidophilus KBL402 (12.90 ± 7.87 pg mL −1 ) ( P < 0.05) or L. acidophilus KBL409 treatment (10.63 ± 2.70%) ( P < 0.05), respectively. Expressions of inflammation-related micro-RNAs (miRs) were also significantly altered in mice with L. acidophilus . Finally, L. acidophilus treatment could restore the diversity of the gut microbiota. Mice with L. acidophilus KBL402 treatment showed a high relative abundance of the genus Akkermansia (0.022 ± 0.017) and Prevotella (0.010 ± 0.006) ( P < 0.01). Butyrate and propionate, the major short-chain fatty acids, in the ceca of DSS + KBL402-treated mice were significantly higher than in that of the mice with DSS-induced colitis (0.03 ± 0.02 ng mg −1 and 0.03 ± 0.01 ng mg −1, respectively) ( P < 0.05). Our study suggests that L. acidophilus KBL402 and KBL409 could be useful for the prevention or treatment of IBDs in various ways including the modulation of immune responses and miR expression, restoration of the gut microbiota, and production of metabolites.